Upaya Peningkatan Pengetahuan Kader Dengan Modul Konseling Kb Pasca Persalinan Berdasarkan Information Motivation Behavioral Skills (IMB) Model - Siti Nurjanah; Erinda Nur Pratiwi; Wijayanti Wijayanti; Atiek Murharyati (Jurnal Salam Sehat Masyarakat (JSSM), 2021)
The application of postpartum birth control is very important because the return of fertility to a mother after giving birth is unpredictable and can occur before the arrival of the menstrual cycle, even in breastfeeding women. The first ovulation in a non-breastfeeding woman can occur as early as 34 days postpartum, even earlier. This causes during breastfeeding, women often experience unwanted pregnancy (KTD / unwanted pregnancy) at intervals close to previous pregnancies. Contraception should be used before sexual activity begins. It is therefore very strategic to start contraception as early as possible after delivery. After efforts to increase knowledge, it is hoped that cadres in the Gambirsari Health Center work area can provide counseling to mothers related to postpartum family planning. Method of implementation with lectures and discussions. The media used are modules, LCDs, laptops, and projectors. The implementation of health education is planned to be carried out at posyandu activities, namely in April-August 2020. The result of community service is that 90% of cadres know and understand better and from the results of monitoring and evaluation by meeting again at Posyandu Kinasih, 90% of cadres can explain the contents of the postpartum family planning counseling module. Based on the implementation of community service, it can be concluded that there is an increase in counseling skills, information, motivation and skills in using family planning at postpartum by cadres in the working area of ​​Puskesmas Gambirsari Surakarta.